1998
DOI: 10.1620/tjem.184.49
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Plasma Peptide YY and Pancreatic Juice Hypersecretion Following Massive Small Bowel Resection in the Rat.

Abstract: To clarify a physiological role of endogenous peptide YY(PYY) on pancreatic exocrine secretion, gastrointestinal transit and bile flow, a hyper-PYY-emia model was constructed by performing a massive small bowel resection using rats. (1) 75% resection of the small intestine was performed at its distal side. Two weeks after surgery, these rats were fed a liquid meal, and intestinal transit of contents was observed and plasma PYY and secretin concentrations were measured by radioimmunoassay. (2) Two weeks after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…In the present study, we found that with TEN, distal bowel resection also results in significant increases in the parameters of enterocyte proliferation. Massive bowel resection reserving distal bowel increases the plasma levels of PYY compared with sham rats [8,9]. These studies suggest that PYY seems to play an important role together with other neurohormonal factors to induce enterocyte proliferation.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In the present study, we found that with TEN, distal bowel resection also results in significant increases in the parameters of enterocyte proliferation. Massive bowel resection reserving distal bowel increases the plasma levels of PYY compared with sham rats [8,9]. These studies suggest that PYY seems to play an important role together with other neurohormonal factors to induce enterocyte proliferation.…”
Section: Discussionmentioning
confidence: 71%
“…This unique distribution makes PYY an ideal candidate for hormonal regulation of upper gastrointestinal function. After massive intestinal resection reserving distal bowel, plasma PYY levels in rats increased markedly after feeding, reaching their peak at 1 h and remaining at higher levels compared to the control (non-surgery) group for the following 5 h [8]. The increase in plasma PYY levels was owing to the reservation of part of the distal small intestine and colon.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…An Mäusen konnte gezeigt werden, dass peripher verabreichtes PYY (3-36) zu einer moderaten Reduktion der Nahrungsaufnahme und leichtem Gewichtsverlust führt [14]. Dieser Sattheit vermittelnde Effekt ist auch in normalund übergewichtigen Menschen nachzuweisen [15] und wird zudem von der Beobachtung gestützt, dass ein Anstieg der Plasmawerte von PYY nach Ileumresektion ebenfalls mit Gewichtsverlust assoziiert werden konnte [16].…”
Section: Peptide Yy (3-36)unclassified